Analysis of Topology and DC Component for a New Type Photovoltaic Grid-connect Inverter - YIN Liang; SONG Pinggang; HU Liu; XU Kai (Kongzhi Yu Xinxi Jishu)
It describes the mechanism of DC component production of photovoltaic (PV) grid-connected inverter system, analyzes the theory of DC component inhibition for single-phase full-bridge topology, H5 topology and a new isolated topology in detail. Simulation results show that the new topology can suppress DC component effectively and can provide a reference for the development of PV grid-connect generation.